Audit of Postoperative Readmissions and Patient Messages following Endoscopic Transnasal Transsphenoidal Surgery - Harary, Maya; Bommakanti, Krishna K.; Nakhla, Morcos N.; Kosaraju, Nikitha; Heaney, Anthony P.; Kim, Won; Lee, Jivianne T.; Suh, Jeffrey D.; Bergsneider, Marvin; Wang, Marilene B. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objectives The aim of this study was to identify the reasons for patient messages, phone calls, and emergency department (ED) visits prior to the first postoperative visit following discharge after endoscopic transnasal transsphenoidal (eTNTS) surgery.Design This is a retrospective review of patients at a tertiary care academic center who underwent eTNTS for resection of a sellar region tumor between May 2020 and August 2021. Patient, tumor, and surgical characteristics were collected, along with postoperative, postdischarge, and readmission information. Regression analyses were performed to investigate risk factors associated with postdischarge phone calls, messages, ED visits, and readmissions.Main Outcome Measures The main outcomes were the number of and reasons for phone calls, patient messages, and ED visits between hospital discharge and the first postoperative visit. We additionally determined whether these reasons were addressed in each patient's discharge instructions.Results A total of 98 patients underwent eTNTS during the study period. The median length of hospital stay was 2 days (interquartile range [IQR]: 1–4 days), at which point most patients (82%) were provided with eTNTS-specific discharge instructions. First postoperative visit took place 9 days after discharge (IQR: 7–10 days). Within that time, 54% of patients made at least one phone call or sent at least electronic message and 17% presented to the ED. Most common reasons for call/message were nasal care, appointment scheduling, and symptom and medication questions.Conclusion Through this work, we highlight the most common reasons for resource utilization via patient phone calls, messages, and ED visits among our cohort to better understand any shortfall or gap in the discharge process that may reduce these events.
Keywords: endoscopic skull base surgery; TNTS; discharge instructions; readmissions